Flavocoxid, a Nutraceutical Approach to Blunt Inflammatory Conditions - Bitto, Alessandra; Squadrito, Francesco; Irrera, Natasha; Pizzino, Gabriele; Pallio, Giovanni; Mecchio, Anna; Galfo, Federica; Altavilla, Domenica (Mediators of Inflammation, 2014)
Flavonoids, from Scutellaria baicalensis (Chinese skullcap) and Acacia catechu (black catechu), have been shown to exert a variety of therapeutic effects, including anti-inflammatory, antiviral, antibacterial, and anticancer activities. Flavocoxid is a mixed extract containing baicalin and catechin and it acts as a dual balanced inhibitor of cyclooxygenase-1 (COX-1) and COX-2 peroxidase enzyme activities with a significant inhibition of 5-lipoxygenase (5-LOX) enzyme activity in vitro. Flavocoxid downregulates gene or protein expression of several inflammatory markers and exerts also strong antioxidant activity in several experimental models. Controlled clinical trials and a postmarketing study have clearly shown that flavocoxid is as effective as naproxen in managing the signs and symptoms of osteoarthritis of the knee and it has better upper gastrointestinal, renal, and respiratory safety profile than naproxen. Flavocoxid may therefore provide a potential therapeutic approach to the treatment of chronic inflammatory conditions.